(untitled) - De Mente, Boye (Lincolnwood, Ill., U.S.A., 1987)
This book introduce about today, problems facing westerners doing business in Japan, the Japan businessman, profile of Japan's business world...
Keywords: Quy ước kinh doanh,Business etiquette; Nhật Bản,Japan